About the Forms of Existence of the Legal Interest of Taxpayer - S. A. Yadrikhinskii (Сибирское юридическое обозрение)
On the basis of doctrinal provisions the article deals with the problem of legal existence of the taxpayer's legal interest. The author analyzes the normative and non-normative (natural-legal) points of view and concludes that these two legal approaches are complementary, not exclusive. Examples of the existence of both objective and subjective legal interest of the taxpayer not implemented in the legislation on taxes and levies are given. The diversity of legal interests of taxpayers allows to distinguish two forms of their existence: textual expression in the rules of law (positivation) and in the consciousness of the taxpayer. At the same time, legal interests that are not mediated by the law are not less protected. The role of the taxpayer in the process of positive legal interests that have not found a normative shell is shown in the framework of the implementation of the principle “everything that is not prohibited by the law is allowed”.